Nanoscale Waveguides in Optical Metamaterials: Jacobi Elliptic Funtion Solutions - Tchier, Fairouz; Aslan, Ebru Cavlak; İnç, Mustafa (Amer Scientific Publishers, 2017)
In this study, we examine the dynamics of soliton propagation from inside nanoscale waveguides in optical metamaterials. The presented model will be discussed by the two non-linear forms. They are models of Power and Kerr laws. For these models, we acquired bright, dark and singular optical solitons by using Jacobi elliptic functions. We obtain the necessary conditions for the existence of obtained optical solitons. Also Jacobi elliptic function solutions are acquired.
Keywords: Solitons; Jacobi Elliptic Functions; Optical Soliton; Kerr Law; Power Law